(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, various pragmatic forms of verbs in speech in Uzbek language are covered. It is known that verbs differ from other word groups in their active use in speech, their pragmatic versatility, and their stylistic and social characteristics. Also, the expressive coloring of verbs is clearly demonstrated in the manner of speech. In the article, the above-mentioned characteristics of verbs are analyzed based on Uzbek fiction and sources in social networks.